Policy Analysis of Civil Servant Mutation on the Needs of Local Government Organizations Based on BKN Regulation No. 5 of 2019 - Mustafa, Adriana; Hisbullah; Sofyan (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2023)
Abstract The implementation of the civil servant mutation policy in the context of the needs of regional government organizations in Gowa Regency is a strategic action carried out by the regional government to transfer employees according to the needs of certain units or departments. Thus, the goal to be achieved is to increase the efficiency and effectiveness of public services by placing employees in positions that suit their abilities and competencies. The research used is field research. This research uses qualitative analysis, intending to provide a systematic description of a phenomenon, symptoms and conditions that occur as well as explaining precisely the conditions that are related to the variables studied. The resulting data shows that the civil servant mutation process must be enforced with strong legal protection, which ensures that all stages of mutation take place fairly, openly and in accordance with applicable regulations. Legal protection for civil servants who experience transfers by the regional government in Gowa Regency includes several important aspects, such as: 1) Principle of Legal Certainty; 2) Transparent Procedures; 3) Consultation and Clarification; 4) Protection from Discrimination and 5) Appeal Mechanism. Keywords: Mutation; Civil Servant; Local Government